2009
DOI: 10.1002/ange.200806221
|View full text |Cite
|
Sign up to set email alerts
|

Carbanion oder Amid? Elektronendichteuntersuchung am 2‐Picolyllithium‐Stammsystem

Abstract: Die negative Ladung als Resultat der Deprotonierung der Methylgruppe wird über den 2‐Picolylring verteilt. Die aus der Elektronendichteverteilung abgeleiteten Bindungseigenschaften zeigen den Enamidcharakter von Picolyllithium (PicLi; Bild: Deformationsdichte von [2‐PicLi⋅PicH]2), wenn auch ein elektrophiler Angriff immer am deprotonierten C‐Atom erfolgt. Dies ist durch das elektrostatische Potential erklärbar, das ein Elektrophil zum nucleophilen Kohlenstoffatom dirigiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
(25 reference statements)
5
35
0
2
Order By: Relevance
“…To reach this conclusion, we compared metal-anion and picolyl C-C and C-N bond distances with those of Stalke's aza-allyl 2-picLi 2-picH species. 8 This shows that in 85 our complex, the single bond/double bond character of the N-C-C unit is more pronounced while crucially, our C-Li bond distances are considerably longer at 2.980 (7) figure 8). …”
mentioning
confidence: 71%
See 1 more Smart Citation
“…To reach this conclusion, we compared metal-anion and picolyl C-C and C-N bond distances with those of Stalke's aza-allyl 2-picLi 2-picH species. 8 This shows that in 85 our complex, the single bond/double bond character of the N-C-C unit is more pronounced while crucially, our C-Li bond distances are considerably longer at 2.980 (7) figure 8). …”
mentioning
confidence: 71%
“…5 allylic) interaction present (figure 3). 8 Meanwhile, Dhau and Singh have reported the -lithiation of 2-picoline and 2,3-lutidine (2,3-dimethylpyridine) using nBuLi as metalating reagent. 9 In this study they noted that prior complexation of the heterocycle with Lewis acidic BF3 effects a 10 greater than 2-fold increase in the yield of electrophilically quenched product.…”
Section: Figurementioning
confidence: 99%
“…Stalke and co‐workers have analyzed the electron density in some organolithium complexes 7. In a recent study,8 they reported the coordination of picoline (PicH) and the picolyl anion (Pic) to Li to form [{PicPicHLi} 2 ] (PicLi; Figure 1). The coordination of Pic is particularly interesting as the electronic configuration of the anion is itself somewhat ambiguous.…”
Section: Methodsmentioning
confidence: 99%
“…[112] The coordination of the anion is of particular interest, as there is a diversity of feasible electronic configurations of Pic À , which is reflected by the variety of different resonance formulas depicted in Scheme 1. In light of the solid-state structures, A and D appear to contribute most to the appropriate description of the bonding; A emphasizes the carbanionic form, whereas D interprets the anion as an enamide.…”
Section: Sulfur-diimide S(nr) 2 and Sulfur-triimide S(nr)mentioning
confidence: 99%